2015
DOI: 10.1002/qj.2698
|View full text |Cite
|
Sign up to set email alerts
|

Impact of seasonal variations in weekday electricity use on urban air temperature observed in Osaka, Japan

Abstract: Seasonal variations in the human activity signal (HAS) affecting the urban temperature were analysed in districts with offices and commercial buildings, apartment buildings, and single-family households in the urban area of Osaka, Japan. Temperatures were observed at building rooftops and at ground level in 14 districts. Spatial and temporal patterns of HAS were identified for a combined spring and autumn intermediate season, the summer cooling season, and the winter heating season by observing the temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…As the AC is operated in all buildings, floors, and rooms in the CTRL, it is very likely that the sensible heat pumped from the outside to inside (negative sensible heat release) is overestimated, which contributes to underestimation of air temperature simulated by the CTRL. Ohashi et al (2016b) observed that surface air temperature on weekdays in Osaka was significantly lower than that on weekends (including holidays) during the winter heating season. They suggested that this temperature difference was caused by differences in human activity, i.e.…”
Section: Improvement Of the Bep+bem Model For A Japanese Megacitysupporting
confidence: 90%
See 3 more Smart Citations
“…As the AC is operated in all buildings, floors, and rooms in the CTRL, it is very likely that the sensible heat pumped from the outside to inside (negative sensible heat release) is overestimated, which contributes to underestimation of air temperature simulated by the CTRL. Ohashi et al (2016b) observed that surface air temperature on weekdays in Osaka was significantly lower than that on weekends (including holidays) during the winter heating season. They suggested that this temperature difference was caused by differences in human activity, i.e.…”
Section: Improvement Of the Bep+bem Model For A Japanese Megacitysupporting
confidence: 90%
“…Ohashi et al . () observed that surface air temperature on weekdays in Osaka was significantly lower than that on weekends (including holidays) during the winter heating season. They suggested that this temperature difference was caused by differences in human activity, i.e.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…1a, Path 2). 22 Using a simple one-dimensional mixing-layer model, Ohashi et al 23 estimated the increase in summertime air temperature from AC waste heat in Osaka City to be +0. 36 to +0.72°C.…”
Section: Introductionmentioning
confidence: 99%